1994
DOI: 10.1002/sapm1994922159
|View full text |Cite
|
Sign up to set email alerts
|

A Perturbation Analysis of an Interaction between Long and Short Surface Waves

Abstract: The interaction of finite-amplitude long gravity waves with a small-amplitude packet of short capillary waves is studied by a multiple-scale method based on the invariance of the perturbation expansion under certain translations. The result of the analysis is a set of equations coupling the complex amplitude of the packet of short waves with.the long-wave velocity potential and surface elevation. The short wave is described by a Ginzburg-Landau equation with coefficients that depend on properties of the long w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Of central interest in the present paper is the asymptotic late time macroscopic behaviour of complex dynamical systems. Previously, Bricmont & Kupiainen have combined asymptotic methods with ideas from renormalisation theory to study problems in diffusive processes and special limiting solutions of nonlinear parabolic equations [3,4,5] while Woodruff has cast multiple timescale problems in the form of renormalisation theory [39,42,40,41]. This allowed the equations governing larger-scale phenomena to be derived from a more general theory and to be separated out from the small scale dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Of central interest in the present paper is the asymptotic late time macroscopic behaviour of complex dynamical systems. Previously, Bricmont & Kupiainen have combined asymptotic methods with ideas from renormalisation theory to study problems in diffusive processes and special limiting solutions of nonlinear parabolic equations [3,4,5] while Woodruff has cast multiple timescale problems in the form of renormalisation theory [39,42,40,41]. This allowed the equations governing larger-scale phenomena to be derived from a more general theory and to be separated out from the small scale dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion is based on the blocking effect of large ka through an effective gravitational acceleration. It is similar to the trapping of free gravity waves between two 'caustics' on a long wave (Phillips 1981;Shyu & Phillips 1990) and the blockage of a free capillary wave packet by a gravity wave (Woodruff & Messiter 1994). In parasitic ripple experiments, however, Yermakov et al (1986) observed a monotonic increase of the maximum ripple steepness θ r with ka.…”
Section: Introductionmentioning
confidence: 86%
“…This interaction happens when the linear dispersion relation is such that the group velocity of a wavetrain of short waves coincides with the phase velocity of the long-wave component (Benney's theory). The earliest studies along this line were made by Nishikawa et al [10], Benney [11], Kawahara and Jeffrey [12] and Woodruff and Messiter [13].…”
Section: Introductionmentioning
confidence: 99%